THE ROOTING OF SOCIAL SECURITY AND ITS APPLICATIONS THROUGH THE SUNNAH OF THE PROPHET - Al-Otaibi, Atallah Muhammad (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2024)
Social security is one of the requirements of life, and there has been a major defect in its understanding and application, especially in our contemporary reality, and the reason for that is ignorance of the teachings and legislation of religion. The researcher wanted to clarify one aspect of the comprehensiveness of the Prophet's Sunnah, and the people's need for it, by demonstrating the originality and interest of the Prophet's Sunnah in addition to social security and its necessity in achieving the security, stability and sustainability of the Islamic society. Using the method of induction and analysis, by mentioning the hadiths that showed this aspect, and the research deals with an introduction to defining social security linguistically and idiomatically, and the value of social security in Islam, and clarifying the characteristics of Islamic society, knowing the principles of social security, the means of applying social security, and knowing the legitimate purposes of them, The researcher reached a statement of the comprehensiveness of the Sunnah and its presentation of solutions to many societal problems, and that the characteristics of the Muslim community, such as obedience to the ruler, and the law of enjoining good and forbidding evil, contribute to increasing social security, as well as the principles of social security such as justice, equality, and consultation are compatible with human instinct towards stability, as well as means Their application is possible and effective.